Patient safety: within the reach of the homeless? - Felicialle Pereira da Silva; Elizandra Cássia da Silva; Adriana Lopes Ferreira; Iracema da Silva Frazão
ABSTRACT Objectives: to reflect on aspects related to homeless patients' safety. Methods: this is a reflective theoretical essay based on patient safety theories. Results: the patient safety culture has developed in the hospital care context and seeks to reduce adverse events in specific hospital settings. On the streets, there is evidence that many people suffer damage related to lack of access to health services, which contributes to undiagnosed or untreated diseases. To build the safety culture it is necessary to identify risks and errors in this scenario since health safety should not start only when hospitalizing an individual. Final Considerations: public policies for this population group need to be effective, as this issue should be a priority concern in health care to prevent harm and adverse events during care delivery.